KEGIATAN YANG DILARANG MENURUT UNDANG UNDANG NOMOR 5 TAHUN 1999 - Fauji Syaputra; Muhammad Wahyudi (Jurnal At-Tabayyun, 2023)
The purpose of this writing is to find out the activities that are prohibited in Law Number 5 of 1999. And it can be useful for readers or business people about activities that are prohibited in Law Number 5 of 1999 such as; monopolistic activities, monopsony activities, market share control, price management and collusion. Basically activities that are monopolistic or result in unfair business competition are prohibited in Law Number 5 of 1999. Because these activities can result in profits for one party and harm for one of the other parties.